Perang Dagang Amerika Serikat dan Tiongkok di Masa Pandemik COVID-19 - Azmi, Fuad (Universitas Padjadjaran, 2021)
The presence of COVID-19 at the beginning of 2020 caused instability in the global economy. This impact was also felt by the United States and China, which were involved as actors in the trade war. New dynamics have emerged amid the COVID-19 pandemic which directly impacts the national economies of the two countries. This paper aims to analyze the efforts of the United States and China in maintaining the economic strength of the two countries through the opportunities and challenges that arise amid the pandemic as a great power country. The discussion is presented through the analytical framework of the concept of struggle of power and zero-sum game in the theory of mercantilism in the study of global political economy. In its preparation, this paper uses qualitative research methods based on descriptive case studies using secondary data collection techniques through literature studies. The results of the study conducted showed that the United States and China have significantly different methods and priority scales in dealing with COVID-19, but have fundamental similarities in the concept of restructuring the country's economy. America's main challenge is still dealing with the country's internal problems, while China's challenge lies in rebuilding its trust and credibility in the eyes of the world. On the other hand, the vulnerability of the global economy in various countries can be an opportunity for great power countries to expand their influence and gain power in the international state system. Where parties who have more influence in the global economy have a higher chance of winning the trade war.Keywords: COVID-19, Trade War, economics, Opportunities, and Challenges